Understanding lncRNAs: key regulators of myogenesis and lipogenesis in farm animals - Liu, Wenjing; Chen, Mengjie; Liu, Yining; Li, Xinxin; Li, Hui; Wang, Jian (Frontiers in Veterinary Science, 2025)
Long non-coding RNAs (lncRNAs) are RNA molecules exceeding 200 nucleotides in length. Recent studies have demonstrated their involvement in regulating gene expression and various biological processes. Among these, myogenesis and lipogenesis are particularly important because of their direct effects on muscle development and fat deposition in farm animals. These processes are crucial for determining meat quality, growth rates, and overall economic value in animal husbandry. Although the specific mechanisms through which lncRNAs influence these pathways are still under investigation, further research into their roles in muscle and fat development is crucial for optimizing farm animal breeding strategies. Here, we review the characteristics of lncRNAs, including their biogenesis, localization, and structures, with a particular focus on their association with myogenesis and adipogenesis. This review seeks to establish a theoretical foundation for enhancing farm animal production. In particular, focusing on lncRNAs may reveal how these molecules can enhance the economic traits of farm animals, thereby contributing to the optimization of farm animal breeding processes.